Diagnostic efficacy of intraoperative histopathological examination of lesions with unknown diagnosis suspicious for malignancy - Tevfik İlker Akçam; Ezgi Köse; Seda Kahraman Aydın; Ahmet Kayahan Tekneci; Dilara Özyiğit Büyüktalancı; Ayşe Gül Ergönül; Ali Özdil; Deniz Nart; Kutsal Turhan; Alpaslan Çakan; Ufuk Çağırıcı (Heliyon, 2023)
Objective: In this study, the efficiency of intraoperative histopathological examination (frozen section examination; FS) in patients operated per suspected lung malignancy was evaluated. Methods: The data of 136 patients who underwent surgery in our clinic due to suspected lung malignancy between January 2020 and June 2021 was evaluated prospectively. Results: The FS was inconclusive in 7.3 % of the 136 patients. In contrast, the accuracy of differentiating between benign and malignant lesions was 99.2 %, while the rate of false negative was 0.8 % in 126 patients with a prediagnosis. FS examination led to an accurate diagnosis in 91.9 % of the 98 patients without a history of extrapulmonary malignancy (EPM), with a false negativity rate of 1 %, whereas a paraffin-embedded examination was recommended in 7.1 %. The accuracy of the FS was 98.9 % in 91 patients prediagnosed based on an FS, with a false negativity rate of 1.1 %. In the same group of patients, the FS examination was successful in establishing the subtype in 32.9 % of the patients with primary lung cancer (PLC), whereas the efficacy of the FS examination in determining the subtype was better in benign diseases (63.6 % vs 32.9 %, p = 0.009). The FS examination was unable to differentiate between benign and malignant lesions in 92.1 % of patients with EPM but differentiated between primary and metastatic lesions in 48.3 % of patients who had malignancy. Furthermore, FS examination successfully guided surgery in 89 patients with no history of EPM (90.8 %) and 20 patients (52.6 %) with a history of EPM. Conclusion: Although FS is insufficient in subtyping lung cancers and distinguishing PLC and metastasis, it is an important and effective diagnostic approach with its overall ability to distinguish benign and malignant lesions and guiding surgical procedures.